Bibliometric analysis of publications trends on the terrorism issues in Indonesia - Gonda Yumitro; Rizki Febriani; Ali Roziqin; Anisa Indraningtyas (Perpustakaan Universitas Gadjah Mada, 2023)
Introduction. The issue of terrorism in Indonesia has been a challenge around the world, particularly in a country with the world's largest Muslim population. This study aims to evaluate the trend of publications on the issue of terrorism in Indonesia in the period starting from 1980 to 2022 through a bibliometric analysis. Data Collection Methods. Data were obtained from the Scopus database using the keywords